Poor post‐exposure prophylaxis completion despite improvements in post‐violence service delivery in 14 PEPFAR‐supported sub‐Saharan African countries, 2018–2023 - Udhayashankar Kanagasabai; Stephanie M. Davis; Viva Thorsen; Emily Rowlinson; Anne Laterra; Jennifer Hegle; Carrine Angumua; Alexandre Ekra; Minlangu Mpingulu; Meklit Getahun; Fikirte Sida; Phumzile Mndzebele; et al. (Journal of the International AIDS Society, 2025)
Abstract Introduction Sexual violence (SV) affects millions globally and has a well‐documented bidirectional association with HIV. Post‐exposure prophylaxis (PEP) is a critical, yet often underutilized, HIV prevention tool in post‐SV care. Despite its potential impact to reduce HIV transmission, SV care remains an overlooked service delivery point for HIV prevention. The U.S. Centers for Disease Control and Prevention (CDC), as part of the President's Emergency Plan for AIDS Relief (PEPFAR), supports PEP provision within broader post‐violence care (PVC) services. Understanding PEP utilization is crucial for optimizing service delivery and HIV prevention efforts. Methods Using Monitoring Evaluation and Reporting data from fiscal years 2018–2023, we conducted a descriptive analysis of clients who received PVC and SV services through CDC‐supported programming in 14 sub‐Saharan African countries. Results From 2018 to 2023, the annual number of clients receiving any PVC, and specifically SV, services increased by 233% (in 2018, n = 206,764; in 2023, n = 689,349) and 163% (in 2018, n = 42,848; in 2023, n = 112,838), respectively. Fewer than half of SV clients completed PEP (38% in 2018, n = 16,103; 31% in 2023, n = 35,118). Across all years combined, most SV clients (female: 185,414; male: 59,618) were aged 15–19 years. The age band and sex with the lowest proportion of clients completing PEP were males aged 15–19 (4%, n = 2296). Conclusions The findings underscore a critical gap between the scaling of SV services and the completion of PEP within violence response programmes. Innovative implementation science approaches may help to identify and address barriers inhibiting effective PEP delivery and uptake within PVC service delivery programmes. Enhancing PEP uptake and completion can support mitigating the bidirectional relationship between violence and HIV acquisition, particularly among vulnerable populations like adolescents and young adults. Low PEP coverage also reflects missed opportunities, particularly among adolescent girls and young women, who experience disproportionate rates of HIV acquisition.